STUDENTS' MATHEMATICAL LITERACY IN SOLVING PROBLEMS SYSTEM OF EQUATION OF THREE VARIABLES - Melisa Melisa; Nida Sri Utami (Pattimura University, 2023)
The main focus in this study aims to analyze the mathematical literacy skills of students at senior high school in solving problems involving the system of linear equations of three variables. The researcher took a qualitative descriptive method. The research subjects were 34 students from class X8. Problem sheets and interviews were the main data collection methods in this study. Researchers reduced data, presented data, and drew conclusions to handle data using a triangulation approach. The indicators of mathematical literacy skills studied were 1) Communication; 2) Mathematization; 3) Strategies in problem solving; 4) Use of language and symbolic operations; formal and technical; 5) Reasoning and argumentation skills. The findings of this study revealed that only one indicator, the communication indicator, was mastered by students in the low mathematical literacy category. Three indicators, namely communication indicators, problem solving techniques and mathematical communication indicators, can be mastered by students with medium mathematical literacy. Students with high mathematical literacy were able to understand and use each sign correctly. Students at SMA Negeri 1 Slogohimo have an average percentage of low mathematical literacy ability of 21%, medium mathematical literacy ability of 18%, and high mathematical literacy ability of 61%